Stimulation of Canine Nucleus Pulposus Cells and Bone Marrow-Derived Stromal Cells with Notochordal Cell-Secreted Factors. (May 2014) - de Vries, S.; Potier, E.; van Doeselaar, M.; Meij, B.; Tryfonidou, M.; Ito, K.
Introduction: Intervertebral disc (IVD) degeneration, a major cause for low back pain, is characterized by a decreasing number of nucleus pulposus cells (NPCs), 1 which are then unable to maintain a healthy disc matrix. Bone marrow-derived stromal stem cells (MSCs) are attractive cells for IVD regeneration because they can acquire a phenotype consistent with NPCs, and injection of MSCs into the IVD has been shown to inhibit the progression of degenerative changes. 2 Current regenerative strategies concentrate on augmenting the effect of the transplanted MSCs or promoting the phenotype of the resident cells (NPCs). In this respect, conditioned medium from notochordal cells, present in the immature IVD (NCCM), has been shown to stimulate NPC metabolism, 3 and modulate differentiation of MSCs toward a NP-like phenotype. 4 The goal of this study was to assess, in a canine in vitro model, the stimulatory effects of NCCM on NPCs, MSCs and their mixture (NPCs + MSCs), as well as the effect of MSCs on NPCs alone. Materials and Methods: Canine MSCs and NPCs were harvested from mature chondrodystrophic dogs (Beagles) and cryopreserved until further use. NCCM was produced from 1- to 1.5-year-old nonchondrodystrophic dogs; healthy canine nucleus pulposus tissue was cultured for 4 days in high glucose (hg)DMEM + 1% pen/strep. MSCs, NPCs, and the combination of both cell types (1:1) were then cultured for 4 weeks in 1.2% alginate beads (MSCs, NPCs alone: 3 million cells/mL; NPC + MSC: 6 million cells/mL) at 37°C, 5% O2, and 5% CO2 . The beads received either base medium (BM: hgDMEM + 5% stripped FCS + 1% pen/strep), NCCM (supplemented with 5% stripped FCS + 1% pen/strep), or positive control medium (TGF: BM + 10 ng/mL TGF-β1). A crossover group (Cr) was given NCCM for 1 week and BM for the remainder of the culture duration to investigate whether short-term exposure to NCCM was enough to promote matrix production. At days 1 and 28, beads were analyzed for cell viability by confocal microscopy (Calcein AM/Propidium iodide staining), for glycosaminoglycan (GAG) and DNA contents by DMMB assay and Qubit Quantification Platform, respectively, and for GAG deposition by Alcian blue staining. Gene expression (Collagen 2, Aggrecan, and SOX9) was determined by RT-qPCR. Statistical analysis was done with a Kruskal-Wallis test followed by a Mann-Whitney U-test with Bonferroni correction for post hoc testing. Statistical significance was assumed for p < 0.05 Results: At days 1 and 28, no notable cell death was observed for any group. When cultured in NCCM, GAG content increased for both NPCs and MSCs, compared with BM (Fig. 1A ). Addition of MSCs to NPCs did not increase GAG content. These findings were confirmed by Alcian blue staining. DNA content decreased compared with day 0 for both cell types and NPC + MSC cultured in BM (Fig. 1B ). DNA content, however, increased for NPC in NCCM compared with BM. TGF-β1 increased GAG (90 µg/bead) and DNA (1.4 µg/bead) content for NPCs and NPCs + MSCs. In contrast, TGF-β1 did not have an effect on MSC GAG production or proliferation. Increased NPC cluster formation was observed with NCCM compared with BM, consistent with the increase in DNA content. Collagen 2 and Aggrecan expression were upregulated for NPCs and NPCs + MSCs in NCCM (8.0-15.5 × day 0) compared with BM (0.8-7.1 × day 0). SOX9 slightly increased with NCCM (up to 4.6 × day 0) compared with BM (up to 2.3 × day 0) in NPCs. MSCs showed a higher upregulation of Collagen 2, Aggrecan, and SOX9 (up to 150, 000 × day 0, 140 × day 0 and 6.3 × day 0, respectively) with no differences between medium conditions. GAG and DNA content as well as gene expression levels in the Cr group were similar to BM. Fig.1 (A ) GAG per bead content at day 28 and (B ) DNA per bead content at days 0 and day 28; p < 0.05 compared with BM; ∗ p < 0.05 compared with day 0. Conclusion: The current results show that bioactive factors secreted by the NCs can promote NPC phenotype: NCCM increased NPC proliferation, gene expression of Collagen 2, Aggrecan, SOX9, as well as GAG production by the NPCs. However, short-term exposure of NPCs to NCCM (Cr group) did not have these stimulatory effects, indicating that either continuous or repeated exposure to NCCM is necessary. MSCs also responded to NCCM, but addition of MSCs to NPCs did not have an additive effect in terms of GAG content, most likely due to the unexpected decreased viability and proliferation of the MSCs. However, we cannot exclude that addition of MSCs may still have a stimulatory effect, considering the increased GAG per DNA ratio for NPCs + MSCs in BM compared with NPCs alone in BM. Though TGF-β1 treatment showed a stronger stimulation of NPCs, the concentration of bioactive factors in NCCM is not known and it may be orders of magnitude lower than the concentration of TGF-β1 used in this study. In conclusion, the use of NC-secreted factors as a therapeutic approach for IVD regeneration seems promising, and identification of these factors would be helpful to further develop this approach. Acknowledgments This work was supported by AOSpine International through an AOSpine Research Network grant (SRN2011_11). Disclosure of Interest None declared References Freemont AJ. The cellular pathobiology of the degenerate intervertebral disc and discogenic back pain. Rheumatology (Oxford) 2009;48(1):5–10 Serigano K, Sakai D, Hiyama A, Tamura F, Tanaka M, Mochida J. Effect of cell number on mesenchymal stem cell transplantation in a canine disc degeneration model. J Orthop Res 2010;28(10):1267–1275 Erwin WM, Inman RD. Notochord cells regulate intervertebral disc chondrocyte proteoglycan production and cell proliferation. Spine 2006;31(10):1094–1099 Korecki CL, Taboas JM, Tuan RS, Iatridis JC. Notochordal cell conditioned medium stimulates mesenchymal stem cell differentiation toward a young nucleus pulposus phenotype. Stem Cell Res Ther 2010;1(2):18